2022
DOI: 10.1021/acs.jpcb.2c04574
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Mutational Response to Track the Evolution of SARS-CoV-2 Spike Variants: Introducing a Statistical-Mechanics-Guided Machine Learning Method

Abstract: The emergence of SARS-CoV-2 and its variants that critically affect global public health requires characterization of mutations and their evolutionary pattern from specific Variants of Interest (VOIs) to Variants of Concern (VOCs). Leveraging the concept of equilibrium statistical mechanics, we introduce a new responsive quantity defined as “Mutational Response Function (MRF)” aptly quantifying domain-wise average entropy-fluctuation in the spike glycoprotein sequence of SARS-CoV-2 based on its evolutionary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Before the pandemic, ML was used extensively in biology [ 25 , 26 , 27 , 28 ], for example, to predict mutations of influenza A viruses by predicting which AA position will mutate [ 29 ] and to predict recurrent mutations in cancer [ 30 ]. ML has been used throughout the SARS-CoV-2 pandemic as a tool to assist vaccine development and predict epitope hotspots [ 31 ]; the binding affinity of antibodies to mutations in the spike RBD [ 32 ]; the binding affinity of chemical compounds as inhibitors against the M-pro protein [ 33 , 34 ]; the clinical disease severity based on the virus genome mutations [ 35 ]; the mutation rate of nucleotide substitution (e.g., A > T) [ 36 ]; the subsequent nucleotide given a sequence of the SARS-CoV-2 genome, and also given a pair of sequences to indicate the location of the changes [ 37 ]; the antibody escape mutations of the spike protein [ 38 ]; the spread of spike protein mutation, based on fold-change per country [ 39 ]; future domain-specific spike mutations [ 40 ]; anti-SARS-CoV-2 activities from molecular structure [ 41 ]; and many more [ 42 , 43 ]. In this article, we start by showing some descriptive statistics of SARS-CoV-2 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Before the pandemic, ML was used extensively in biology [ 25 , 26 , 27 , 28 ], for example, to predict mutations of influenza A viruses by predicting which AA position will mutate [ 29 ] and to predict recurrent mutations in cancer [ 30 ]. ML has been used throughout the SARS-CoV-2 pandemic as a tool to assist vaccine development and predict epitope hotspots [ 31 ]; the binding affinity of antibodies to mutations in the spike RBD [ 32 ]; the binding affinity of chemical compounds as inhibitors against the M-pro protein [ 33 , 34 ]; the clinical disease severity based on the virus genome mutations [ 35 ]; the mutation rate of nucleotide substitution (e.g., A > T) [ 36 ]; the subsequent nucleotide given a sequence of the SARS-CoV-2 genome, and also given a pair of sequences to indicate the location of the changes [ 37 ]; the antibody escape mutations of the spike protein [ 38 ]; the spread of spike protein mutation, based on fold-change per country [ 39 ]; future domain-specific spike mutations [ 40 ]; anti-SARS-CoV-2 activities from molecular structure [ 41 ]; and many more [ 42 , 43 ]. In this article, we start by showing some descriptive statistics of SARS-CoV-2 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…To follow the evolution of SARS-CoV-2, various efforts have been made to set up an epidemiological surveillance system using information theory due to the S protein gaining many mutations. Recently, we showed how crucial it is to analyze domain-wise mutational entropy to comprehend the evolution of viruses . We described a new responsive quantity called mutational response function (MRF) that, based on its evolutionary database, accurately quantifies domain-wise average entropy-fluctuation in the spike glycoprotein sequence of SARS-CoV-2.…”
Section: Studies Of 1d Sequence Evolution Using Information Theorymentioning
confidence: 99%
“…We found that the evolutionary crossover from a particular variety to a VOC is accompanied by a significant shift in MRF, maintaining the hallmark of a dynamic phase transition. The details of the MRF description can be found elsewhere . Using viral genomic and protein sequences, our method creates a pipeline that can be used to follow the evolution of any variant.…”
Section: Studies Of 1d Sequence Evolution Using Information Theorymentioning
confidence: 99%
See 2 more Smart Citations